2009
DOI: 10.3945/jn.109.104844
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids May Mediate the Ability of (n-3) Fatty Acids to Reduce Ectopic Fat and Inflammatory Mediators in Obese Zucker Rats

Abstract: Dietary (n-3) long-chain PUFA [(n-3) LCPUFA] ameliorate several metabolic risk factors for cardiovascular diseases, although the mechanisms of these beneficial effects are not fully understood. In this study, we compared the effects of dietary (n-3) LCPUFA, in the form of either fish oil (FO) or krill oil (KO) balanced for eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) content, with a control (C) diet containing no EPA and DHA and similar contents of oleic, linoleic, and alpha-linolenic acids, on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
212
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(227 citation statements)
references
References 53 publications
13
212
2
Order By: Relevance
“…17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs. Finally, there is an in vitro study showing that n-3 PUFA can reduce the levels of both anandamide and 2-AG in differentiated mouse adipocytes, whereas n-6 PUFAs (that is, arachidonic acid) were found to increase endocannabinoid levels.…”
Section: Discussionmentioning
confidence: 95%
“…17,[40][41][42] Also the fatty acid composition of dietary fat may influence endocannabinoid action. 43 For example, the presence or absence of n-3 PUFAs in the diet affects endocannabinoid levels in the brain, as shown by Berger et al 44 and Watanabe et al 45 Batetta et al 46 recently found that dietary n-3 PUFAs can reduce inflammatory markers and liver triglyceride levels, and these effects were associated with lower levels of endocannabinoid ligands in peripheral organs. Finally, there is an in vitro study showing that n-3 PUFA can reduce the levels of both anandamide and 2-AG in differentiated mouse adipocytes, whereas n-6 PUFAs (that is, arachidonic acid) were found to increase endocannabinoid levels.…”
Section: Discussionmentioning
confidence: 95%
“…Correspondingly, ω-3 PUFAenriched diet during pregnancy lowers 2-AG and AEA levels in the fetus (48). ω-3 PUFA intake is also beneficial for insulin secretion and sensitivity (49)(50)(51). Here, we hypothesized that lowering eCB levels during pregnancy and lactation might be reflected in a mixed cell-pancreatic phenotype and improved hormonal responses to glucose in the offspring.…”
Section: -Ag Signaling Modulates β Cell Survival In Pancreatic Pseudmentioning
confidence: 99%
“…Supplemental -3 fatty acid intake (including DHA) can reduce cell and tissue levels of AA and AA-derived downstream metabolites, including AEA and/or AG potentially due to substrate competition among biosynthetic enzymes ( 12,16,23,24,32,46,47 ). Alternatively, diets low in -3 and rich in -6 fatty acids (including AA) have been shown to increase AA-derived AEA and AG in mouse and piglet brain ( 24,31 ).…”
Section: -3 -6 and -9 Metabolitesmentioning
confidence: 99%